2018
DOI: 10.1017/s0033291718002271
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic minority position and migrant status as risk factors for psychotic symptoms in the general population: a meta-analysis

Abstract: Psychotic symptoms (PS) are experienced by a substantial proportion of the general population. When not reaching a threshold of clinical relevance, these symptoms are defined as psychotic experiences (PEs) and may exist on a continuum with psychotic disorders. Unfavorable socio-environmental conditions, such as ethnic minority position (EMP) and migrant status (MS), may increase the risk of developing PS and PEs. We conducted an electronic systematic review and a meta-analysis assessing the role of EMP and MS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
35
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 114 publications
(115 reference statements)
4
35
1
1
Order By: Relevance
“…Our lifetime prevalence estimate was significantly higher for Arabs than non-Arabs and did not significantly differ between Arab migrants and non-migrants, but was substantially lower for non-Arab migrants. Migration was not a factor in determining PEs in our sample, which is consistent with findings from a recent meta-analysis (Leaune et al, 2018), but counter to some studies that indicate migration, social adversity, and negative social experience may be cumulative, particularly in migrant groups, in predisposing to PEs (Bourque, Ven, andMalla, 2011) andpsychosis (McKenzie et al, 2008). The context of where the migrant moves to is important, as the high rates of PEs and psychosis reported in second-generation immigrants has been attributed to psychosocial adversity (e.g.…”
Section: Discussionsupporting
confidence: 91%
“…Our lifetime prevalence estimate was significantly higher for Arabs than non-Arabs and did not significantly differ between Arab migrants and non-migrants, but was substantially lower for non-Arab migrants. Migration was not a factor in determining PEs in our sample, which is consistent with findings from a recent meta-analysis (Leaune et al, 2018), but counter to some studies that indicate migration, social adversity, and negative social experience may be cumulative, particularly in migrant groups, in predisposing to PEs (Bourque, Ven, andMalla, 2011) andpsychosis (McKenzie et al, 2008). The context of where the migrant moves to is important, as the high rates of PEs and psychosis reported in second-generation immigrants has been attributed to psychosocial adversity (e.g.…”
Section: Discussionsupporting
confidence: 91%
“…However, these health trends seem to deteriorate with years spent in the host country and over time migrant health statuses become closer to the native-born population, as has been observed in Canada and elsewhere [2,3,31]. Racism [10,34], poor living and working conditions [35,36], stresses of integration [17,37], unemployment, lack of social networks and lack of access to services [11] or health care [38], and more globally, deprivation [38], are all factors of vulnerability associated with immigration and reasons for health to decline among recent immigrants. In general, new immigrants experience poor socioeconomic conditions, which may lead to a deteriorating health status, and even after improvement of social conditions, their health status declines to become similar to the Canadian-born population [3] (p.108).…”
Section: Introductionmentioning
confidence: 99%
“…Traub (2017) reported that 79% of forensic psychiatric patients in Baden‐Württemberg forensic psychiatric care were foreign nationals. The literature provides strong evidence that ethnic minority groups from certain world regions are diagnosed with schizophrenia at a much higher rate than others, and there are also substantial correlations among migration, social disadvantage, and the prevalence of schizophrenia (Dykxhoorn et al, 2019; Leaune et al, 2019).…”
Section: Discussionmentioning
confidence: 99%